2010
DOI: 10.1111/j.1600-0528.2010.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring pathways for socio-economic inequalities in self-reported oral symptoms among Korean adolescents

Abstract: There were clear social gradients in three self-reported oral symptoms (toothache, bad breath and fractured teeth) in Korean adolescents. Psychosocial factors explained part of the social inequalities in oral symptoms. Future longitudinal research is required to better address the pathways that explain socio-economic inequalities in oral symptoms during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
3
17
0
1
Order By: Relevance
“…Recent models partially explain socioeconomic health inequality through contextual factors which operate at family and community-level domains (31,32,44). An increasing body of evidence shows the effects on oral health of family function, social support, social capital, physical environment, sense of coherence, and coping with stress (44)(45)(46)(47)(48)(49)(50). Unfortunately, information on such factors has not been routinely collected until recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Recent models partially explain socioeconomic health inequality through contextual factors which operate at family and community-level domains (31,32,44). An increasing body of evidence shows the effects on oral health of family function, social support, social capital, physical environment, sense of coherence, and coping with stress (44)(45)(46)(47)(48)(49)(50). Unfortunately, information on such factors has not been routinely collected until recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, local studies have shown the prevalence estimates from 25.6% to 35.7% (Borges & Gottlieb, ; Goes et al, ; Noro, Roncalli, Mendes Júnior, Lima, & de, & Teixeira, A. K. M., ; Peres, Peres, Frias, & Antunes, ; Santiago, Valença, & Vettore, ; Schuch, Correa, Torriani, Demarco, & Goettems, ). Among the factors associated with pain in developing as well as in developed countries are demographic, socioeconomic, family, psychosocial and cultural factors, as well as the oral health condition and related behaviours (Bastos, Gigante, Peres, & Nedel, ; Bastos et al, ; Borges et al, ; Escoffié‐Ramirez et al, ; Freire et al, 2012; Jung, Watt, Sheiham, Ryu, & Tsakos, ; Kiwanuka & Åstrøm, ; Lahti, Sipilä, Taanila, & Laitinen, ; Lewis & Stout, ; Nomura, Bastos, & Peres, ; Noro et al, ; Pau, Croucher, & Marcenes, ; Schuch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…13 Some researchers have found no association between TDI and socioeconomic status, 15,17 whereas others have found an association between TDI and a less privileged socioeconomic status. 18,19 Thus, divergent findings are reported in the literature, which underscores the importance of further studies addressing the relationship between TDI and socioeconomic status.…”
mentioning
confidence: 99%
“…4,27 Considering the advances in the concept of oral health as perceived by adolescents and not merely that identified by dentists, regarding the biological aspects of the health/illness process, the present investigation was undertaken to broaden the discussion on the impact of TDI on the quality of life of adolescent students and to clarify of the association between TDI and socioeconomic factors. 15,[18][19][20] In addition, etiological factors were addressed to gain a better understanding of environmental and cultural aspects that contribute to the occurrence of this adverse oral health condition.…”
mentioning
confidence: 99%